A prospective study of number of attempts required in conventional image guided transthoracic fine needle aspiration for pulmonary lesions - Sagar, Ramesh C.; Kumar, K. V. Veerendra; Madhu, S. D.; Malathi, M. (International Surgery Journal, 2019)
Background: With the established role of computed tomography (CT) screening for lung cancer, and the broad application of high-resolution CT, the solitary pulmonary nodule (SPN) are increasingly detected. The discovery rate of pulmonary lesions is evidently elevated these days: most of them are benign, but some of them are lung cancer. Lung cancer remains the leading cause of cancer deaths worldwide. The diagnosis of this pulmonary lesion is difficult and obtaining tissue samples to conduct pathology examination is the key point. Image guided transthoracic fine needle aspiration (TTFNA) of lung lesions is a well established, safe, and rapid method for achieving a definitive diagnosis for most lung lesions. Methods: TTFNA were performed in 160 patients attended the OPD and admitted due to pulmonary lesions between September 2016 and May 2017. After detailed characterization by computed tomography and compared with chest x-ray, TTFNA was done. Number of attempts, reasons for multiple attempts, and final FNAC diagnosis were recorded. Results: When CT guidance was used sufficient material was obtained in 91.03% of patients, but with USG guidance insufficient material was reason for repeated attempts in nearly 25.25% of cases. Bloody aspirate was reason in total 13.54% patients and there was no significant difference between CT guidance and USG guidance (14.29% v/s 13.13% respectively). Again only inflammatory cells was reason for repeated attempts, in CT guidance 8.93% and in USG guidance 20.20%, attributed to localization of needle in both techniques. Conclusions: CT guided FNAC should be considered in diagnosis of lung lesions if computerized tomography is not contraindicated. Further, routine need for advanced imaging techniques like 3D computerized tomographic study for localizing lesions in lung to reduce the number of attempts should be considered.